Analisis Spasial Kerawanan Banjir Bandang Berdasarkan Karakteristik Fisik Wilayah Menggunakan Pendekatan SIG di Pulau Bali - Fajrina Akmalia; Dinda Parasnalurita; Julia Armita Parenja; Mawaddah R.; Adhi Munajar (Mataram University, 2026)
The combination of complex volcanic topography and local rainfall fluctuations places Bali in a position that is quite vulnerable to flash floods. Based on these conditions, this study attempts to map the level of regional vulnerability through an approach to its physical environmental characteristics using a Geographic Information System (GIS). The method used is descriptive quantitative, relying on a series of spatial analyses—starting from classification, weighting (scoring and weighting), to overlay techniques. Slope data from DEMNAS with a spatial resolution of 8 meters and annual rainfall data from BMKG are the two main parameters in this study. From the mapping results, the Bali region is divided into three levels of vulnerability: a low zone covering 170,249.34 ha (30.45%), a medium zone which dominates at 372,112.04 ha (66.55%), and a high zone covering 16,807.95 ha (4.66%). Interestingly, areas with high levels of vulnerability are concentrated in mountainous areas such as Bangli Regency, Karangasem, and parts of Tabanan. This is triggered by the intersection of steep slopes and high-intensity rainfall. Ultimately, these findings can provide a strong foundation for designing disaster mitigation strategies and risk-based spatial planning management on the island of Bali.